Scaffolding to Help Middle School Students' Critical Thinking Skill in Solving Social Arithmetic Material - tazkia, savirra; Siswono, Tatag Yuli Eko (Universitas Negeri Surabaya, 2022)
Junior high school students in completing social arithmetic material often fail to think critically, so they need help using scaffolding to help critical thinking skill. This qualitative research is a case study of two junior high school students who failed to think critically. Data were obtained through task-based interviews. The tests used in this study were 2 social arithmetic questions that required students' critical thinking skills in solving them. Data analysis used the flow model analysis technique developed by Miles and Huberman (2014) which consisted of data collection, data reduction, data presentation, and drawing conclusions. The researcher uses research diligence to ensure the credibility of the data. The results of this study indicate that Subject 1's critical thinking failure lies in the components of interpretation, and inference. Subject 2 failed to think critically on the components of interpretation, analysis, evaluation, inference, and explanation. The scaffolding given to overcome the failure of critical thinking in subject 1 and subject 2 is the Anghileri’s level 2 scaffolding, namely explaining, reviewing, and restructuring.